Greece's Investment Gap - Hua, Shiqing (IMF Working Papers; Working Paper, 2022)
Greece's investment rate plunged following the Sovereign Debt Crisis (SDC) and remained one of the lowest in the world in 2019. This paper explores recent investment dynamics and compares them against estimated benchmarks. Our results suggest that Greece has been under-investing since the SDC, with private investment notably lagging behind. The estimated investment gap ranges from 1.6-8 percent of GDP in 2019. Structural impediments have constrained corporate investment, while business cycle and balance sheet developments have held back household investment. Structural reforms are recommended to remove bottlenecks to corporate investment, improve efficiency of public investment, and boost household investment.